The Cooperation of Russia and China in Central Asia - I. Safranchuk (Международная аналитика)
This article is devoted to the cooperation of Russia and China in Central Asia. The article studies the options for agreed implementation of Russia-sponsored Eurasian Economic Union and China-sponsored Economic belt of Silk Road.